Is There an Influence of the Pole Tide on Volcanism? Insights From Mount Etna Recent Activity. Issue 23 (3rd December 2019) - Lambert, S.; Sottili, G.
Abstract: We investigate a possible link between polar motion and (i) seismic energy release and (ii) timing and intensity of eruptions at Mount Etna (Italy) for which a dense observational database is available. Our study suggests that the seismicity around Mount Etna increases during the largest excursions of the Earth rotation pole, which result from the constructive interference of the climate‐driven seasonal and Chandler wobbles. To a lesser extent, a similar link is detected between the pole tide and the erupted volume of magma. We infer that, by creating periodic changes in the state of stress in the crust through a variable centrifugal force and a periodic vertical displacement (pole tide), variations in polar motion influence eruption timing and magnitude and the rate of seismic energy release from volcanoes. This study provides new evidences on the sensitivity of volcanoes to external forcing. Plain Language Summary: The Earth surface is continuously deformed by a wide range of phenomena including lunisolar tides and centrifugal forces due to changes in the Earth's rotation rate and in the direction of its rotation axis. The latter class of deformations is typically of a centimeter on interannual timescales. On another side, some volcanoes appear to be sensitive to small perturbations of the crustal stress. We detected similar variability in the centrifugal forces arising from the Earth's rotation axis direction variability and Mount Etna seismicity and erupted magma volume. This suggests that the variation of the Earth's rotation axis direction plays a significant role as modulator of the activity of Mount Etna. Key Points: Seismicity and eruption timing and magnitudes at Mount Etna show interannual variations in phase with the solid Earth pole tide Earth's Chandler and annual wobbles may alter the state of stress of the Earth's crust at interannual to decadal timescales